DETERMINANTS OF POVERTY IN 10 PROVINCES IN SUMATRA ISLAND - Zainul hamzah; Toto Gunarto; Marselina Marselina; I Wayan Suparta (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Poverty is a complex and multidimensional problem and cannot be seen easily only from an absolute number. The problem of provincial poverty is inseparable from various aspects in each region. In this study, the problem of poverty is studied in the province of Sumatra island. Sumatra Island has 10 provinces. This study aims to determine the effect of macroeconomic variables, namely the quality of human resources, income inequality and the level of open unemployment on the percentage of poor people in 10 provinces on the island of Sumatra. This study uses a combined Panel Data from data between time series and regional observations, where the time series (time series) used in this research is in the 2017-2021 period, using regional observations or (cross section) covering the area of Aceh, North Sumatra. , South Sumatra, West Sumatra, Riau, Jambi, Riau Islands, Bangka Belitung Islands and Lampung. In this study, secondary data were obtained from the Central Statistics Agency (BPS). This research uses Panel Data Regression Method. The results showed that the quality of human resources had a negative and significant influence, income inequality and the open unemployment rate had a positive and significant impact on the percentage of poor people in 10 provinces on the island of Sumatra.